On the convergence of solutions of inclusions containing maximal monotone and generalized pseudomonotone mappings. (September 2016) - Le, Vy Khoi
Abstract: We are concerned in this paper with the existence, boundedness, and the convergence of solutions to a sequence of inclusions A k ( u ) + B k ( u ) ∋ L k, where A k is a maximal monotone mapping, B k is a generalized pseudomonotone mapping defined on a reflexive Banach space X, and L k ∈ X ∗ . We study appropriate kinds of convergence for A k and B k such that a limit of a sequence of solutions of these inclusions is also a solution of the limit inclusion.